Driving immunity: all roads lead to metabolism - Pearce, Edward J. (Nat Rev Immunol, 2017)
In 2017, studies of cellular metabolism broadly permeated immunological research. Accumulating data support the view that understanding how metabolism regulates immune cell function could provide new therapeutic opportunities for the many diseases associated with immune system dysregulation.